How do tenascins influence the birth and life of a malignant cell? - Brellier, Florence (Blackwell Publishing Ltd, 2012)
Tenascins are large glycoproteins found in embryonic and adult extracellular matrices. Of the four family members, two have been shown to be overexpressed in the microenvironment of solid tumours: tenascin-C and tenascin-W. The regular presence of these proteins in tumours suggests a role in tumourigenesis, which has been investigated intensively for tenascin-C and recently for tenascin-W as well. In this review, we follow a malignant cell starting from its birth through its potential metastatic journey and describe how tenascin-C and tenascin-W contribute to these successive steps of tumourigenesis. We consider the importance of the mechanical aspect in tenascin signalling. Furthermore, we discuss studies describing tenascin-C as an important component of stem cell niches and present examples reporting its role in cancer therapy resistance.